Determinant of Eï¬€ective Family Communication among First-Grade High School Adolescents Aged 15 - 16 Years: A Multi-Centre Cross-sectional Study - Heni Dwi Windarwati; Retno Lestari; Ridhoyanti Hidayah; Ahmad Afif Supianto; Satrio Agung Wicaksono; Niken Asih Laras Ati; Mira Wahyu Kusumawati; Dewa Ayu Anggi Gharbelasari; Ridwan Sofian; Phat Prapawichar (Jurnal Keperawatan Padjadjaran, 2022)
Background: Family communication can become a support system for adolescents. Ineï¬€ective communication in the family causes emotional problems and poor psychological well-being in adolescents. Purpose: This study aimed to analyze the determinant factor of eï¬€ective family communication in adolescents. Methods: This was a cross-sectional multi-centre design with 357 participants aged 15-16 from fve high schools in Indonesia. We used the convenience sampling method to select participants. Communication in the family questionnaire, Rosenberg Self Esteem Instrument, Depression Anxiety Stress Scale (DASS-21), and the Scale for Suicide Ideation (SSI) questionnaires were used to measure communication within the family, selfesteem, stress, anxiety, depression, and suicide ideation, respectively. Data were analyzed using Chi-square and binary logistics regression. Results: Most of the adolescents were male (52.1%), had harmonious families (96.6%), had economic status above the minimum wage (65.5%), had high self-esteem (88.5%), and had high social support (67.8%). However, in terms of mental health problems, as many as 47.3%, 74.2%, 72%, and 30.5% of adolescents experienced stress, anxiety, depression, and suicidal ideation, respectively. The multivariate analysis concluded that gender (AOR: 0.499; 95% CI: 0.294-0.847) and socioeconomic status (AOR: 0.2.162; 95% CI: 1.296-3.608) were signifcantly correlated with family communication. Conclusion: Males adolescents are more likely to have ineï¬€ective family communication than female adolescents. Also, adolescents with a family socioeconomic status below the minimum wage have a greater risk of ineï¬€ective family communication. Therefore, it is essential to improve family communication through assertive communication training in adolescents and families in the educational and community setting.